2021
DOI: 10.1002/slct.202004215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bio‐Based Aldehyde Structure on the Conversion and Selectivity Towards Glycerol Acetal Over Amberlyst‐46 by Using a Solvent‐Free Approach

Abstract: Acetalization of glycerol with acetone (1 : 5) at 60 °C catalyzed by A‐46 (10 wt %) under nitrogen (N2) afforded 63 % solketal 1 a in just 15 min. Subsequently, acetalization of glycerol and bio‐based aldehydes i. e. acetaldehyde, isobutyraldehyde, n‐heptaldehyde, p‐anisaldehyde and benzaldehyde were investigated under optimized reaction conditions. The conversion and selectivity of this reaction was found to be affected by structure of aldehydes employed. Excellent conversion of 97 and 99 % were obtained usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Analysis of the crude reaction mixture indicated that the reaction proceeded to furnish 2‐phenyl‐1,3‐dioxolane‐4‐methanol ( 1 ) as a mixture of four conformational isomers [ cis ‐ and trans ‐1,3‐dioxolane ( A ) and cis ‐ and trans ‐1,3‐dioxane ( B )] which is in accordance with other findings 17,20 . The distribution of isomers was determined by the integration of the NMR peak area of C2‐methine (Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Analysis of the crude reaction mixture indicated that the reaction proceeded to furnish 2‐phenyl‐1,3‐dioxolane‐4‐methanol ( 1 ) as a mixture of four conformational isomers [ cis ‐ and trans ‐1,3‐dioxolane ( A ) and cis ‐ and trans ‐1,3‐dioxane ( B )] which is in accordance with other findings 17,20 . The distribution of isomers was determined by the integration of the NMR peak area of C2‐methine (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Without use of solvent, miscibility of the reagents is critical; based on our observations, solketal and benzaldehyde were miscible at room temperature. By contrast, direct acetalization between glycerol and benzaldehyde yielded only 24% product at 60 °C 20 …”
Section: Resultsmentioning
confidence: 92%
“…65 In comparison acetalizations occurring in pyrolysis oil have probably conversions below 75%, due to the complexity of the matrix and the less than optimal conditions. The aldehydes in pyrolysis oil possessing a high molar mass display significantly lower concentrations than in the referred experiments 66–68 where specific catalysts were used. Additionally, the water content in pyrolysis oil might reduce the available aldehydes due to hydration.…”
Section: Resultsmentioning
confidence: 74%
“…In the case of smaller aldehydes higher conversions could be attained. 67,68 Glycerol can lead to cyclic acetals that are entropically favoured. 65 In comparison acetalizations occurring in pyrolysis oil have probably conversions below 75%, due to the complexity of the matrix and the less than optimal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, for the acetal derived from benzaldehyde, 66% of the acetals formed were fivemembered rings and only 34% were six-membered rings. This greater selectivity observed for five-membered rings can be explained by the observation that in the five-membered ring the substituent on the acetal is as far away as possible from other groups, while in the six-membered ring, the substituent is in the axial position, which causes a repulsive 1,3-diaxial type interaction 40,41 (Fig. 4).…”
Section: Evaluation Of Other Aldehydesmentioning
confidence: 97%